Analysis of organochlorine pesticides in suspended solid using ultrasonic solvent extraction and gas chromatography - Abd. Razak, Nur Fadzilah (2014)
Suspended solids in the aqueous environment can become carrier of microorganic pollutants, which may lead to the accumulation and give a toxicity impact towards the environment and human health. A suitable methodology for pesticide residue analysis in suspended solid river water sample was investigated in this study based on ultrasonic extraction (USE) and gas chromatography (GC). Sampling was conducted between May 2013 and June 2014 at sampling site from the water intake point of Syarikat Air Johor Water Treatment Plant of Sungai Skudai. Suspended solid were obtained after the river water samples were filtered using reduced cellulose filter membrane and were extracted using USE technique. The presence of organochlorine pesticide (OCPs) which are aldrin, dieldrin and endrin was determined using gas chromatography mass selective detector (GC-MSD). However, the presence of OCPs was not detectable in all the water samples investigated. An alternative approach has been taken by analyzing the samples using liquid chromatography-tandem mass spectrometry (LC-MS-MS). However, the presence of OCPs was still not detectable. Therefore, for quantitative analysis, three selected OCPs were spiked into the sample (50 µg/L) for determination of optimum condition for extraction in suspended solid using USE technique with regards to solvent types and sonication time. The limit of detection of OCPs were from 0.144 to 0.154 µg/L and the optimum condition for extraction of OCPs in suspended solid was by using ethyl acetate as extraction solvent with 30 minutes of extraction time. The recoveries obtained were in the range of 62.4% to 101.8% with RSDs of less than 15%. The green chemistry sample preparation technique and low toxicity solvents employed in this extraction technique are thus recommended for routine environmental monitoring analysis.